2009
DOI: 10.1016/j.mehy.2008.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics of panic during a bioterrorist attack – A mathematical model

Abstract: A bioterrorist attacks usually cause epidemics of panic in a targeted population. We have presented epidemiologic aspect of this phenomenon as a three-component model--host, information on an attack and social network. We have proposed a mathematical model of panic and counter-measures as the function of time in a population exposed to a bioterrorist attack. The model comprises ordinary differential equations and graphically presented combinations of the equations parameters. Clinically, we have presented a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…Agroterorizam se može definisati kao oblik bioterorizma 1,2 , koji namernom indukcijom bolesti biljaka ili životinja ima za ciljeve stvaranje ekonomskih gubitaka, straha i narušavanje unutrašnje stabilnosti napadnute zemlje [3][4][5][6][7][8] . Podrazumeva namerno ili preteće korišćenje virusa, bakterija, gljivica ili toksina živih organizama (prirodnih ili genetski modifikovanih) u svrhu izazivanja smrti ili oboljenja životinja ili biljaka 9 .…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Agroterorizam se može definisati kao oblik bioterorizma 1,2 , koji namernom indukcijom bolesti biljaka ili životinja ima za ciljeve stvaranje ekonomskih gubitaka, straha i narušavanje unutrašnje stabilnosti napadnute zemlje [3][4][5][6][7][8] . Podrazumeva namerno ili preteće korišćenje virusa, bakterija, gljivica ili toksina živih organizama (prirodnih ili genetski modifikovanih) u svrhu izazivanja smrti ili oboljenja životinja ili biljaka 9 .…”
Section: Uvodunclassified
“…Ciljevi agroterorizma su dvojaki: direktni (biljke, životinje) i indirektni (ekonomski gubici, strah, politička nesta-bilnost) [4][5][6][7][8]12 . Kada se izvrši agroteroristički napad na domaće životinje, napadnuta zemlja mora sprovesti mere karantina i masovnih klanja i spaljivanja zaražene stoke.…”
Section: Ciljevi Agroterorizmaunclassified
“…Loving et al described that mice species were more efficient for the study of anthrax [27]. Radosavljevic et al suggested the curing techniques for the bioterrorist attack of anthrax [28]. Mathematical techniques were studied to analyze the transmission of infectious diseases [29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%